SRI SURYA PAHAR: ARCHAEOLOGICAL SIGNIFICANCE AND CULTURAL HERITAGE OF ASSAM - Ahmed, Gias Uddin (International Journal of Research -GRANTHAALAYAH, 2025)
Sri Surya Pahar, situated in the Goalpara region of Assam, is a magnificent monument of historical and archaeological value. Even though it is only 132 kilometers from Guwahati, it is still not given enough attention in the mainstream discourse on archaeology and heritage. The hilltop location, which is revered by Buddhists, Jains, and Hindus, offers proof of various religious customs from the early Common Era. This essay highlights the merging of various religions and cultures in ancient Assam by analyzing the significance of Sri Surya Pahar through its rock-cut temples, stupas, inscriptions, and sacred sculptures. (Choudhury, 2013, p. 65) The study makes use of secondary data sources, including internet repositories, research papers, journals, and archeological reports. The study emphasizes Sri Surya Pahar as an important cultural heritage site by examining historical, theological, and archaeological evidence. It also examines its applicability to comprehending Kamarupa region cultural continuity, architectural customs, and religious syncretism. (Chakrabarti, 2006, p. 103)